PENGABAIAN PEMBERIAN NAFKAH SUAMI PADA ISTRI SEBAGAI ALASAN PERCERAIAN MENURUT IBNU HAZM - Ahmad Nabil Atoilah; Tsamrotul Rohmah (Fakultas Syari'ah | Institut Agama Islam Darussalam | IAID | Ciamis, Jawa Barat, Indonesia, 2018)
Marriage is a matter of essence for man, all human beings have a sexual instinct, if this is not regulated then it can become wild like an animal. Therefore Islam arranges it in detail in the Shari'ah from the tips of choosing a spouse, Islamic guidance in the wedding, and around the life of the household in order to avoid self-harm or the community. One of the things that often happens in the issue of marriage is the lack of economic or